The Effect of Training and Career Development on Employee Performance - Nabila Gibran; Danny Ramadani (Almana : Jurnal Manajemen dan Bisnis, 2021)
Job knowledge, skills, and morals in a particular organization. So, nowadays many organizations consider employee training and career development as an important part of human resource management. The purpose of this study is to determine the effect of training on employee performance, to determine the effect of career development on employee performance, to determine the effect of training and career development on employee performance. The research method used is descriptive and verification. Respondents in this study were 106 employees of the Karawang District Health Office. Data collection techniques used are observation, interviews, and questionnaires. The data analysis method used is the multiple linear regression analysis. Data analysis was carried out using SPSS 16. The results of this study indicate that training and career development have a weak and unidirectional relationship. Then for the regression results, partially training has a positive influence on employee performance. Career development has a significant influence on employee performance. Simultaneously training and career development affects employee performance.